Measuring Achievement Striving via a Situational Judgment Test : The Value of Additional Context - Golubovich, Juliya, (Colegio Oficial de Psicólogos de Madrid, 2020)
The study extends personality and situational judgment test (SJT) research by using an SJT to measure achievement striving in a contextualized manner. Employed students responded to the achievement striving SJT, traditional personality scales, and workplace performance measures. The SJT was internally consistent, items loaded on a single factor, and scores converged with other measures of achievement striving. The SJT provided incremental criterion-related validity for the performance criteria beyond less-contextualized achievement striving measures. Findings suggest that achievement- related work scenarios may provide additional criterion-relevant information not captured by measures that are less contextualized.